Effect of Ammonium:Nitrate Application Ratios on Growth and Nitrogen Metabolism of Tea Plants (Camellia sinensis L.) - Takuo Enomoto; Natsuki Tone; Takaya Ishii; Hisako Hirono; Ayako Oi; Yuhei Hirono; Takashi Ikka; Hiroto Yamashita (Plant Direct)
ABSTRACT Tea plants (Camellia sinensis L.) use ammonium and nitrate as the main sources of nitrogen (N), but they respond differently to these two compounds. In this study, we investigated the effect of the ammonium:nitrate ratio on tea plant growth as well as N uptake and metabolism. A kinetics analysis showed that both ammonium and nitrate were absorbed, with no major differences within the concentration range 0.71–2.86 mM. Additionally, growth peaked when the ammonium:nitrate ratio was 25:75. The concentrations of several free amino acids, including theanine, in new leaves and roots increased as the proportion of ammonium increased. Glutamine concentrations in new leaves and roots were highest at ammonium:nitrate ratio of 25:75. Moreover, the transcription of key genes involved in theanine and glutamine biosynthesis was differentially affected by changes in N ratios, which explained the differences in metabolic changes. The glutamine:theanine ratio was higher at an ammonium:nitrate ratio of 25:75 than at 100:0 and 75:25, suggesting that the ammonium:nitrate ratio may affect the ratio of glutamine synthesis activity to theanine synthesis activity. We examined N metabolism regulatory genes and identified candidate genes, including SENSITIVE TO PROTON RHIZOTOXICITY 3.1 and NITRATE‐INDUCIBLE GARP‐TYPE TRANSCRIPTIONAL REPRESSOR 1.2, in tea plants. These transcription factor genes are involved in the regulation of nitrate absorption and metabolism. Identifying genes that regulate N metabolism is essential for improving N use efficiency. The study findings will be useful for optimizing N fertilization management practices to control tea growth and quality.